Advanced Research in Pediatric Radiology and Nuclear Medicine - Ng, Curtise K.C (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Advancements in medical imaging modalities have resulted in increasing the importance and demand of pediatric radiology. This reprint showcases various examples of advanced research in pediatric radiology and nuclear medicine. These include the use of medical imaging modalities such as computed tomography, general radiography, magnetic resonance imaging, positron emission tomography, single-photon emission computed tomography, and ultrasound for diagnosis, as well as the performance of artificial intelligence (AI) in computer-aided detection and diagnosis in the pediatric population. The radiation dose issue of pediatric radiological examinations and emerging AI technology for dose reduction, as well as the use of three-dimensional printing based on medical images for pediatric surgical planning, healthcare professional education, and patient-clinician communication are also covered.